Microglial exosome TREM2 ameliorates ferroptosis and neuroinflammation in alzheimer’s disease by activating the Wnt/β-catenin signaling - Ling Zhu; Tao Zhou; Lei Wu; Xuanang Zhu; Lvan Chen; Mi Zhang; Jing Zhou; Fan Wang (Scientific Reports)
Abstract Microglia and exosomes are intimately connected with the pathogenesis of Alzheimer’s disease (AD). We aim to investigate the role and potential mechanisms of M2-like (anti-inflammatory) microglia-derived exosomes (M2-Exos) in AD. We utilized an Aβ1−42-induced AD model in HT-22 neurons and mouse. The effects of M2-Exo on mitochondrial damage, ferroptosis, oxidative stress, and inflammation levels in the AD cell/animal models were evaluated using transmission electron microscopy, immunoblotting, and biochemical assay kits. Cognitive function in mouse was assessed through behavioral tests. In the AD cell/animal models, the effects of M2-Exo on the Wnt/β-catenin pathway were investigated through immunofluorescence and immunoblotting. AD cells were treated with HLY78 (Wnt/β-catenin pathway activator) to explore the modulation of the pathway. After knocking down TREM2 in M2-Exo, mitochondrial damage, ferroptosis, oxidative stress, and inflammation markers were reevaluated in AD cell and animal models. Aβ1−42 induced mitochondrial shrinkage and deformation in neurons, upregulated ACSL4, PTGS2, Fe2+/Fe, lipid peroxide (LPO), ROS, MDA, IL-6, IL-1β, and TNF-α, while it downregulated GPX4, FTH1, and GSH-PX. M2-Exo reversed the effects induced by Aβ1−42 both in vitro and in vivo, and M2-Exo improved cognitive function in AD mouse. HLY78 also reversed the effects induced by Aβ1−42. M2-Exo increased the levels of β-catenin. BV2 cells converting to M2-like type increased TREM2 levels. Knocking down TREM2 in M2-Exos resulted in decreased neuronal β-catenin levels, reversing the beneficial effects of M2-Exo on AD cell and mouse models. M2-Exo TREM2 alleviates neuronal ferroptosis, inflammation, and oxidative stress in AD by activating the Wnt/β-catenin signaling pathway.